Pengaruh Budaya Emosional Kebahagiaan Terhadap Kebahagiaan di Tempat Kerja : Peran Ketahanan sebagai Mediator pada Generasi Z di Sektor Swasta - Endah Wulan Safitri (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study examines the influence of emotional happiness culture on workplace happiness, with resilience as a mediating factor, among Generation Z employees in the private sector. As Generation Z enters the workforce, their unique emotional needs and challenges necessitate a deeper understanding of psychological factors that contribute to workplace well-being. Using a quantitative survey approach, data from 110 private sector Generation Z workers were analyzed to test the direct effects of emotional happiness culture on workplace happiness and resilience, as well as the mediating role of resilience between these variables. Results indicate that a positive emotional culture significantly enhances both resilience and workplace happiness. Moreover, resilience partially mediates the relationship, suggesting that resilience strengthens the impact of emotional culture on employees’ happiness. These findings highlight the importance of fostering an emotional culture that promotes positive emotions such as joy, empathy, and optimism to build resilient and satisfied young employees. This research contributes practical insights for organizations aiming to design psychologically supportive workplaces tailored to Generation Z, ultimately improving employee well-being and organizational sustainability.